Roles of functional groups of naproxen in its sorption to kaolinite. (November 2015) - Yu, Chenglong; Bi, Erping
Graphical abstract: Highlights: The sorption of naproxen to kaolinite occurred on the surfaces of siloxane. Electron donor–acceptor and hydrogen bond can account for naproxen sorption. Diaromatic rings of naproxen are π-electron acceptors. Siloxane oxygens of kaolinite are n-donors. Conceptual model is built to assess naproxen sorption to kaolinite. Abstract: The sorption of acidic anti-inflammatory drugs to soils is important for evaluating their fate and transformations in the water–soil environment. However, roles of functional groups of ionisable drugs onto mineral surfaces have not been sufficiently studied. In this study, batch experiments of naproxen (NPX, anti-inflammatory drug) and two kinds of competitors to kaolinite were studied. The Kd of naproxen to kaolinite is 1.30–1.62 L kg −1 . The n–π electron donor–acceptor (n–π EDA) interaction between diaromatic ring of naproxen (π-electron acceptors) and the siloxane oxygens (n-donors) of kaolinite is the dominant sorption mechanism. The carboxyl group of naproxen can contribute to the overall sorption. A conception model was put forward to elucidate to sorption mechanisms, in which the contribution of n–π EDA and hydrogen bond to overall sorption was quantified. These sorption mechanisms can be helpful for estimating the fate and mobility of acid pharmaceuticals in soil–water environment.